Recent Advances in the Management of Autosomal Dominant Polycystic Kidney Disease - Chebib, Fouad T. (Clin J Am Soc Nephrol, 2018)
Autosomal dominant polycystic kidney disease (ADPKD), the most common monogenic cause of ESKD, is characterized by relentless development of kidney cysts, hypertension, and destruction of the kidney parenchyma. Over the past few years, major advancements in diagnosing, prognosticating, and understanding the pathogenesis and natural course of the disease have been made. Currently, no kidney disease is more suitable for nephron-protective strategies. Early nephrology referral and implementation of these strategies may have a substantial effect. Total kidney volume is a good prognostication marker and allows stratification of patients into slow or rapid progressing disease, with implications for their management. Measurement of total kidney volume, disease stratification, and prognostication are possible using readily available tools. Although some patients require only monitoring and basic optimized kidney protective measures, such as rigorous BP control and various lifestyle and dietary changes, others will benefit from disease-modifying treatments. Vasopressin V2 receptor antagonists, a likely disease-modifying treatment, has been approved in several countries and recently by the US Food and Drug Administration; other therapies, such as somatostatin analogs and other novel agents, are currently in clinical trials. The purpose of this article is to present our views on the optimal management to delay kidney disease progression in ADPKD.